EFEKTIVITAS METODE DEMONSTRASI DAN DRILL PADA PEMBELAJARAN KALIGRAFI DI TPA ASJADI DARUSSA’DAH BIREUEN - Sulhan Yus; Cut Bulan Purnama; Nadiatul Khaira; Faradhila Faradhila; Miftahul Jannah (Yayasan An-Nur Meunara Baro, 2025)
The ability to write Arabic writing or calligraphy is a must to be mastered by every Muslim. However, in reality, the science of calligraphy is only mastered by a small group of Muslims. This study aims to introduce the science of calligraphy to santri at TPA Asjadi Darussa'dah Bireuen. This research uses a qualitative approach with descriptive methods. Data were collected through observation and documentation. The data were then analyzed through data collection, data reduction, and presentation of conclusions. The results showed that the demonstration and drill methods were effective in teaching calligraphy to the students of TPA Asjadi Darussa'dah Bireuen. This can be seen from the number of students who have mastered the writing of single hijaiyah letters in khat naskhi style, out of 39 students, 28 of them have the ability to recognize and write hijaiyah letters in the form of khat naskhi. Of course, this is a positive trend, considering the very small number of meetings. This result is proof that the demonstration and drill methods are feasible and suitable to be applied in calligraphy learning.